The Influence of Price Perception, Religiosity, and Halal Label on Online Purchase Decisions of Skintific Halal Skincare (Case Study on UINSU Students) - Wafiyahningrum Wafiyahningrum; Marliyah Marliyah; Nurul Jannah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to examine the influence of price perception, religiosity, and halal labels on the online purchasing decisions of Skintific halal skincare products among students at Universitas Islam Negeri Sumatera Utara (UINSU). This research employed a quantitative approach using a survey method. The study involved 100 active UINSU students selected through purposive sampling, consisting of respondents who had purchased Skintific halal skincare products online. Data were collected using a structured questionnaire and analyzed through multiple linear regression with the assistance of SPSS 25 software. The findings indicate that price perception, religiosity, and halal labels have a positive and significant effect on online purchasing decisions, both partially and simultaneously. Price perception emerged as the most dominant predictor of purchasing decisions, as indicated by the highest regression coefficient (B = 0.427) and the largest t-value (t = 12.241; p < 0.001), followed by religiosity (B = 0.272; t = 7.352) and halal labels (B = 0.243; t = 7.003). Furthermore, the coefficient of determination (R² = 0.797) indicates that 79.7% of the variance in purchasing decisions is explained by the three independent variables, while the remaining 20.3% is influenced by other factors outside the research model. These findings suggest that online purchasing decisions for halal skincare products are shaped by a combination of economic considerations, religious values, and trust in halal certification. The study provides practical implications for halal skincare producers and marketers to strengthen competitive pricing strategies, maintain credible halal certification, and develop marketing approaches that align with the religious values of Muslim consumers.